Knowledge, Attitude, Practice, and Associated Factors of Postoperative Pain Management Among Nurses - Bereket Samuel; Man Ye (Pain Research and Management)
Conclusion: The study highlights critical gaps in nurses’ knowledge and practices regarding postoperative pain management, particularly in opioid safety, dose conversion, and withdrawal symptoms. Over half of the nurses had inadequate knowledge, and most exhibited poor practices. Although negative attitudes were prevalent, training, experience, and personal pain exposure contributed to improved practices. Enhancing structured education, clinical mentoring, and institutional support is essential to improve postoperative pain care.